2000
DOI: 10.1006/dbio.2000.9761
|View full text |Cite
|
Sign up to set email alerts
|

Too Much Interference: Injection of Double-Stranded RNA Has Nonspecific Effects in the Zebrafish Embryo

Abstract: We have investigated the ability of double-stranded RNA (dsRNA) to inhibit gene expression in a vertebrate, the zebrafish, Danio rerio. Injection of dsRNA corresponding to the T-box gene tbx16/spadetail (spt) into early wild-type embryos caused a rapid and dramatic loss of tbx16/spt mRNA in the blastula. mRNAs from the papc, tbx6, and gata1 genes, which depend on tbx16/spt function for their expression, were reduced, apparently mimicking the spt mutant phenotype. However, mRNAs from a number of genes that are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
106
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(110 citation statements)
references
References 40 publications
3
106
0
Order By: Relevance
“…The vasa dsRNA-injected embryos had neither significant decrease in the number of vasa RNA-expressing cells nor of Vasa protein-expressing cells compared with the controls (data not shown). Our RNAi results are in general agreement with Oates et al (2000), who tested the effect of dsRNA injection in zebrafish and did not observe a specific phenotype related to the targeted mRNA.…”
Section: Resultssupporting
confidence: 91%
“…The vasa dsRNA-injected embryos had neither significant decrease in the number of vasa RNA-expressing cells nor of Vasa protein-expressing cells compared with the controls (data not shown). Our RNAi results are in general agreement with Oates et al (2000), who tested the effect of dsRNA injection in zebrafish and did not observe a specific phenotype related to the targeted mRNA.…”
Section: Resultssupporting
confidence: 91%
“…It has been reported that off-target effects can be a potential problem for RNAi [47][48][49]. We first demonstrated that limited or no cross reactivity occurs between FREP2 and myoglobin, and then showed that with FREP subfamilies non-specific knockdown of expression was not observed except for FREP6.…”
Section: Discussionmentioning
confidence: 81%
“…A few years ago, RNA interference seemed to be a promising new approach for specifically inactivating genes in zebrafish (Wargelius et al 1999;Li et al 2000), but success rates in zebrafish were low and varying, with reports of major nonspecific effects on embryonic development reported as well (Oates et al 2000;Zhao et al 2001). The most widely used reverse genetics method in zebrafish is undoubtedly the use of morpholinos that are targeted to the translation initiation site of a specific transcript, thereby inhibiting its translation (Nasevicius and Ekker 2000).…”
mentioning
confidence: 99%